Effect of novel formulation of Bacillus thuringiensis var. kurstaki (DOR Bt-127) against semilooper (Achaea janata) in castor: Effect of novel formulation of Bacillus thuringiensis var. kurstaki (DOR Bt-127) against semilooper (Achaea janata) in castor - V VINEELA,; P S VIMALA DEVI,; P DURAIMURUGAN, (Journal of Oilseeds Research, 2020)
Semilooper, Achaea janata feeds on many different species of plants among which castor is one of the mostpreferred hosts. DOR Bt-127 was multiplied through solid state fermentation and subjected to milling in a planetary ball mill. 559 nm particles of Bt technical gave 100% mortality against A. janata @ 0.6 mg/l. Field evaluation of Bt127 SC (33.3%) formulation lowered A. janata larval population (97.3 to 98.1% reduction over control by 3 days after treatment).